The Use of Solicited Publishing by Academic Surgeons - Nguyen, Vi (Surgery, 2018)
BACKGROUND: Few details are known about open-access surgery journals that solicit manuscripts via E-mail. The objectives of this cross-sectional study are to compare solicitant surgery journals with established journals and to characterize the academic credentials and reasons for publication of their authorship. METHODS: We identified publishers who contacted the senior author and compared their surgery journals with 10 top-tier surgical journals and open-access medical journals. We assessed the senior authorship of articles published January 2017–March 2017 and utilized a blinded survey to determine motivations for publication. RESULTS: Throughout a 6-week period, 110 E-mails were received from 29 publishers distributing 113 surgery journals. Compared with established journals, these journals offered lesser publication fees, but also had lesser PubMed indexing rates and impact factors (all P < .002). Professors, division chiefs, and department chairs were the senior authors of nearly half of US-published papers and spent ≈$83,000 to publish 117 articles in journals with a median impact factor of 0.12 and a 33% PubMed indexing rate. Survey responses revealed a dichotomy as 43% and 57% of authors published in these journals with and without knowledge of their solicitant nature, respectively. The most commonly reported reasons for submission included waived publication fees (50%), invitation (38%), and difficulty publishing elsewhere (12%) CONCLUSION: Despite their sparse PubMed indexing and low impact factors, many senior academic faculty publish in solicitant surgery journals. This study highlights the importance for the academic surgical community to be cognizant of the quality of a journal when reviewing the literature for research and evidence-based practice.